2008
DOI: 10.1017/s0272263108080327
|View full text |Cite
|
Sign up to set email alerts
|

BIDIRECTIONAL CROSSLINGUISTIC INFLUENCE IN L1-L2 ENCODING OF MANNER IN SPEECH AND GESTURE: A Study of Japanese Speakers of English

Abstract: Whereas most research in SLA assumes the relationship between the first language (L1) and the second language (L2) to be unidirectional, this study investigates the possibility of a bidirectional relationship. We examine the domain of manner of motion, in which monolingual Japanese and English speakers differ both in speech and gesture. Parallel influences of the L1 on the L2 and the L2 on the L1 were found in production from native Japanese speakers with intermediate knowledge of English. These effects, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(171 citation statements)
references
References 27 publications
9
159
0
Order By: Relevance
“…Athanasopolous (2007) found that their Japanese-English bilingual speakers were mainly L2 like and are likely to have acquired the English shape-bias in physical object classification. Brown and Gullberg (2008) found that their Japanese-English participants' co-speech gestures, produced when describing motion events, were gradually shifting towards L2-like behaviors. These studies point to a complex picture of the mental representations in the bilingual mind.…”
Section: Prior Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Athanasopolous (2007) found that their Japanese-English bilingual speakers were mainly L2 like and are likely to have acquired the English shape-bias in physical object classification. Brown and Gullberg (2008) found that their Japanese-English participants' co-speech gestures, produced when describing motion events, were gradually shifting towards L2-like behaviors. These studies point to a complex picture of the mental representations in the bilingual mind.…”
Section: Prior Studiesmentioning
confidence: 97%
“…Studies investigating thinking-forspeaking and relativity effects in bilingual and second-language learner populations have looked at the domains of time (Boroditsky 2001;Lai 2005), physical object (Athanasopolous 2007), and motion (Brown and Gullberg 2008;Gullberg 2011), among others.…”
Section: Prior Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestures also mirror information structure and align with newsworthy or focused information. This coordination means that gestures reflect language-specific meaning in different gestural forms and gestural timing relative to speech (Brown & Gullberg, 2008;Duncan, 2005;Gullberg, Hendriks, & Hickmann, 2008;Kita, 2009;Kita & Özyürek, 2003;McNeill, 1992; (Gullberg, submitted-a). For instance, native French speakers' gestures tend to express the path element of the movement in a simple pointing hand or a gesture with a flat hand shape moving in a given direction.…”
Section: Placement Verbs Across Languages and Modalitiesmentioning
confidence: 99%
“…Pavelnko (1999) defines convergence as a type of language change in which an intermediate system emerges in the bilingual mind, containing elements from both languages, having as an end result, a linguistic system that is different from either of the languages when spoken by monolinguals. For example, Brown and Gullberg (2008) found that when tested on word choice and gesture in speech production in each language, Japanese-English bilinguals performed differently from both their Japanese and…”
Section: -Bilingual Interactionmentioning
confidence: 99%